PERAN DAN FUNGSI SATUAN PENGAWASAN INTERN DALAM PENCEGAHAN FRAUD PADA PERGURUAN TINGGI X - Muhammad Asyim Asya'ri; - Prasetyono; Bambang Haryadi (JAFFA, 2013)
The purpose of this research is to analyze and evaluate of the role and function of Internal Control Unit (SPI) PTN X on the prevention of fraud. The method of this research is qualitative approach with using case study. The unit analysis of this research is the internal control unit in University X. The analyze research used descriptive analysis.The results show that the role and function of SPI has not been preventing fraud. This is because the process of supervision and auditing done by SPI have not led to five pillars of internal control recommended by COSO. Audit conducted by SPI is still compliance test and still financial management risk based. The low environment control and the lack of consciouseness of management against the role and function of SPI causes SPI does not capable to prevent fraud. Some other factors that cause SPI could not reach its maximum function are:   the role conflict of SPI officers, budget that has not been independently managed, and the SPI position in OTK that has not been providing bargaining power and adequate control accessibility.